IMPLEMENTASI AKAD IJARAH DI BANK MUAMALAT BOGOR - Zahid Mubarok (Institut Agama Islam Sahid Bogor, 2022)
Ijarah contracts are contracts that are widely used in Islamic banking, this is because the fee (ujrah) on ijarah contracts is a solution for interest in conventional banking. Almost all Islamic banks in Indonesia apply this contract, including Bank Muamalah Indonesia. How is the implementation of the ijarah contract at Bank Mumalah Indonesia? This study uses a qualitative approach with data obtained directly from the Bogor branch office. Observations and interviews as well as document studies were carried out to obtain a valid description of the object of research.This research shows that the ijarah contract at Bank Muamalah Indonesia is applied in the form of service products, especially in financing and other household services that are very much needed by the community. The ujrah (fee) charged to customers is generated from negotiations with the bank. Most customers are satisfied with this contract because they avoid transactions that contain usury.